Making Simple Bookkeeping Reports Using Microsoft Excel (Case Study: Ball_Mart Taman Cipto Cirebon) - Suwandi, Suwandi; Turini, Turini; Akbari, Safitri; Amroni, Amroni (Institute of Accounting Research and Novation (IARN), 2024)
The purpose of this research is to provide a simple financial reporting solution for Ball_Mart Taman Cipto, Cirebon City. This type of research is qualitative research using descriptive methods. Data collection was carried out using interviews, documentation, literature studies and observation. The main finding of this study is that in making sales reports, cash-in reports still use manuals. The solution provided is the creation of a simple financial reporting application for Ball_Mart Cipto Park, Cirebon City. This application is expected to help Ball_Mart management in running its business. The novelty of this study is that researchers observe bookkeeping report activities made by Ball_Mart, examine problems in the field of making financial reports, and provide solutions.